Constructing the brief diagnostic criteria for temporomandibular disorders (bDC/TMD) for field testing - Durham, Justin (2024)
Background: Despite advances in temporomandibular disorders' (TMDs) diagnosis, the diagnostic process continues to be problematic in non-specialist settings. Objective: To complete a Delphi process to shorten the Diagnostic Criteria for TMD (DC/TMD) to a brief DC/TMD (bDC/TMD) for expedient clinical diagnosis and initial management. Methods: An international Delphi panel was created with 23 clinicians representing major specialities, general dentistry and related fields. The process comprised a full day workshop, seven virtual meetings, six rounds of electronic discussion and finally an open consultation at a virtual international symposium. Results: Within the physical axis (Axis 1), the self-report Symptom Questionnaire of the DC/TMD did not require shortening from 14 items for the bDC/TMD. The compulsory use of the TMD pain screener was removed reducing the total number of Axis 1 items by 18%. The DC/TMD Axis 1 10-section examination protocol (25 movements, up to 12 sets of bilateral palpations) was reduced to four sections in the bDC/TMD protocol involving three movements and three sets of palpations. Axis I then resulted in two groups of diagnoses: painful TMD (inclusive of secondary headache), and common joint-related TMD with functional implications. The psychosocial axis (Axis 2) was shortened to an ultra-brief 11 item assessment. Conclusion: The bDC/TMD represents a substantially reduced and likely expedited method to establish (grouping) diagnoses in TMDs. This may provide greater utility for settings requiring less granular diagnoses for the implementation of initial treatment, for example non-specialist general dental practice.